ANALISIS YURIDIS PERBUATAN MELAWAN HUKUM OLEH PEMERINTAH TERHADAP PENCOPOTAN JABATAN KEPALA DINAS KESEHATAN KOTA BENGKULU (STUDI KASUS PUTUSAN NO. 13/G/2021PTUN-BKL) - Nurjihan Rizkhita; Paulinus Salvator Tarigan; Rio Taufik Ansori (Universitas Stikubank, 2023)
This article discusses the judicial analysis of unlawful acts by the government in the removal of the head of the Bengkulu City Health Service based on Decision No. 13/G/2021 PTUN-BKL. Specifically, the unlawful act by the government in the decision was in the form of issuing a decree that was declared contrary to legal provisions and the AUPB. In this paper, the method used is normative-juridical. The normative-juridical approach can be explained as an approach to solving problems based on law. The results of the study explain that the application of the principle of legality of authority is very important in carrying out the duties and authorities of the government to prevent unlawful acts by the government.